Mechanical Properties Analysis of Stainless Steel 304 Linear Guide Rail Using Autodesk Inventor and MATLAB - Muhammad Azizi; Kurniawan Kurniawan; Deni Shidqi Khaerudini; Gerald Ensang Timuda; Nono Darsono; Nuwong Chollacoop (Universitas Mercu Buana, 2025)
This study investigates the mechanical properties of a stainless steel 304 linear guide rail using a combination of Autodesk Inventor and MATLAB. The primary objective is to analyze the von Mises stress distribution, displacement, and safety factor of the linear guide rail under varying load conditions, as well as to develop a model representing the relationship between stress and strain. A detailed 3D model of the guide rail was created using Autodesk Inventor, followed by finite element analysis (FEA) to evaluate stress and strain distribution across different sections of the rail. The simulation was conducted to assess the structural response under multiple loading scenarios, ensuring its reliability for real-world applications. Furthermore, a linear regression analysis was performed using MATLAB to establish a predictive model correlating stress and strain, enabling more accurate forecasting of the material's mechanical behavior. The results revealed that the maximum von Mises stress obtained from the simulation was 23.595 MPa, with a corresponding maximum displacement of 0.397 mm. The safety factor analysis confirmed the rail's structural integrity, with a minimum safety factor of 10.595, well above the failure threshold. These findings indicate that the linear guide rail meets the necessary mechanical performance requirements for its intended application.